The role of specific information about the verb in parsing sentences with local structural ambiguity - Mitchell, D.C; Holmes, V.M (Journal of memory and language, 1985)
Three experiments were conducted to determine whether individual words can influence the course of parsing in an on-line subject-paced reading task. The materials were sentences with local structural ambiguities. The results of Experiment I showed that when one verb in a sentence was replaced by another, this produced a garden-path effect. This suggests that the identity of the verb may have influenced the choice of structure for the ambiguous phrase. Experiments II and III were conducted to rule out alternative explanations based on possible segmentation artifacts and on changes in the overall plausibility of the sentences. The evidence supported the initial interpretation in terms of a general and robust parsing bias. The findings throw light on the kinds of information that the parser would have to act on when processing the verb.